2008
DOI: 10.1590/s0102-09352008000100029
|View full text |Cite
|
Sign up to set email alerts
|

Nível de proteína bruta para codornas de corte durante o período de crescimento

Abstract: RESUMOEstudou-se a exigência de proteína bruta de codornas de corte na fase de crescimento. Foram utilizadas 288 codornas européias EV2, de ambos os sexos em delineamento experimental inteiramente ao acaso, cujos tratamentos consistiram de dietas com seis níveis de proteína bruta (23, 25, 27, 29, 31 e 33%) e quatro repetições de doze codornas por unidade experimental. Estudaram-se o ganho de peso (g), peso corporal ao final de cada período (g), consumo alimentar (g) e conversão alimentar (g/g) do nascimento ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
1
2
1
7
Order By: Relevance
“…According to Diambra & McCartney (6) birds submitted to diets deficient in protein tend to increase consumption to compensate for this deficiency. Result similar to this work was reported by Corrêa et al (7) , that evaluating CP levels in diets for European quails from 1 to 21 days of age, found that higher feed intake was observed for quails fed 31% CP in diets. Teixeira et al (8) observed that 18.41% of CP in diet with 2550 kcal of ME kg -1 decreased feed intake of quails from 1 to 21 days of age and suggested that levels increased of CP and ME, can occur increased in feed intake.…”
Section: Resultssupporting
confidence: 92%
“…According to Diambra & McCartney (6) birds submitted to diets deficient in protein tend to increase consumption to compensate for this deficiency. Result similar to this work was reported by Corrêa et al (7) , that evaluating CP levels in diets for European quails from 1 to 21 days of age, found that higher feed intake was observed for quails fed 31% CP in diets. Teixeira et al (8) observed that 18.41% of CP in diet with 2550 kcal of ME kg -1 decreased feed intake of quails from 1 to 21 days of age and suggested that levels increased of CP and ME, can occur increased in feed intake.…”
Section: Resultssupporting
confidence: 92%
“…reported a linear decrease in meat-type quail WG and BW at 14 d of age by increasing dietary AMEn levels from 2,800 to 3,100 Kcal/kg. Contrary to our results, however, Corrêa (2007) did not observe detrimental effects of AMEn levels on 7-to-21-day-old meat-type quail BW and WG by ranging dietary AMEn from 2,900 to 3,100 Kcal/kg.…”
Section: Resultscontrasting
confidence: 99%
“…Entretanto, Oliveira et al (2002), ao testarem cinco níveis de proteína (18,20,22, 24 e 26%) e três de energia (2.800, 3.000 e 3.200kcal de EM/kg) para codornas, verificaram que, para o máximo ganho em peso no período total de cinco a 49 dias de idade, as rações deveriam conter 26% de PB e 3.200kcal de EM/kg. Contudo, Corrêa et al (2008), ao estudarem efeito dos níveis de proteína bruta no peso corporal de codornas de corte, observaram que aves alimentadas com maiores níveis de PB (30%) apresentaram maior peso corporal do nascimento até 21 dias de idade. De maneira contrária, Veloso et al (2012) não observaram efeito dos níveis de proteína bruta sobre o ganho em peso de codornas de corte na fase inicial de crescimento.…”
Section: Resultsunclassified